Editorial: venom collection - Sakthivel Vaiyapuri; Patrizia Falabella (Scientific Reports)
Abstract Venoms are naturally available biological resources with a huge potential to explore numerous pharmacologically valuable compounds to diagnose and treat human diseases. Therefore, researching venoms is not only beneficial to develop better diagnostic and therapeutic approaches for envenomation, but also to explore the clinical potential of a plethora of molecules. This special Collection includes a range of articles that report a variety of research on the development of diagnostic methods for venom detection and toxicity of venoms in various cellular systems. We believe that this Collection extends the knowledge and offers potential avenues to initiate new lines of research in this field.